Poder suave y diplomacia pública en el contexto multilateral - Landelius, Peter (Revista Mexicana de Política Exterior, 2012)
Soft power has gained increasing importance in the world that has emerged from the rubble of the Berlin Wall, yet it is a concept that is as hard to implement as it is to define, for diplomacy is soft power par excellence. Historically, says Peter Landelius, soft power has been treated mainly as a subject for bilateral representations and is sometimes confused with traditional types of propaganda or marketing. By way of contrast, multilateral diplomacy —increasingly necessary in today’s multi-polar, globalized world— seeks ways to address a growing number of shared problems and its powers are essentially “soft”, although this elusive power has many and varied applications. Small and medium countries are particularly interested in the subject, but superpowers, too, are beginning to acknowledge its importance. The European Union —the first union of States created in the absence of violence— remains the world’s prime example of soft power.